Solvent Use in Private Research Laboratories in Japan: Comparison with the Use in Public Research Laboratories and on Production Floors in Industries. Issue 5 (22nd November 2014) - Hanada, Takaaki; Zaitsu, Ai; Kojima, Satoshi; Ukai, Hirohiko; Nagasawa, Yasuhiro; Takada, Shiro; Kawakami, Takuya; Ohashi, Fumiko; Ikeda, Masayuki
Abstract : Solvent Use in Private Research Laboratories in Japan: Comparison with the Use in Public Research Laboratories and on Production Floors in Industries: Takaaki HANADA, et al . Kyoto Industrial Health Association— Background and Objectives: Solvents used in production facility‐affiliated private laboratories have been seldomly reported. This study was initiated to specify solvent use characteristics in private laboratories in comparison with the use in public research laboratories and on production floors. Elucidation of the applicability of conclusions from a public laboratory survey to private institutions is not only of scientific interest but also of practical importance. Materials: A survey on use of 47 legally stipulated organic solvents was conducted. The results were compiled for April 2011 to March 2013. Through sorting, data were available for 479 unit workplaces in private laboratories. Similar sorting for April 2012 to March 2013 was conducted for public research laboratories (e.g., national universities) and production floors (in private enterprises) to obtain 621 and 937 cases, respectively. Sampling of workroom air followed by capillary gaschromatographic analyses for solvents was conducted in accordance with regulatory requirements. Results: More than one solvent was usually detected in the air of private laboratories. With regard to solvent types, acetone, methyl alcohol, chloroform and hexane were prevalently used in private laboratories, and this was similar to the case of public laboratories. Prevalent use of ethyl acetate was unique to private laboratories. Toluene use was less common both in private and public laboratories. The prevalence of administrative control class 1 (i.e., an adequately controlled environment) was higher in laboratories (both private and public) than production floors. Conclusions: Solvent use patterns are similar in private and public laboratories, except that the use of mixtures of solvents is substantially more popular in private laboratories than in public laboratories.